Feasibility of a mobile app to improve inhaler adherence in real‐world patients with asthma: A multicentre observational study in Portugal and Spain - Jácome, Cristina (2021)
InspirerMundi app aims to transform adherence into a positive experience through gamification and social support, while allowing objective monitoring of inhaler adherence. This study assessed the feasibility of the app in adolescents and adults with persistent asthma.